Outcome measurement in patients with low back pain undergoing epidural steroid injection - ŞANAL TOPRAK, CANAN; GÜNDÜZ, OSMAN HAKAN (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2019)
Objectives: This study aims to evaluate the outcomes of epidural steroid injection (ESI) in patients with low back pain. Patients and methods: This prospective study included a total of 82 patients (51 females; 31 males; mean age 50.8 +/- 14.2 years; range, 17 to 86 years) who underwent ESI due to lumbar disc hernia-induced radiculopathy between September 2014 and May 2015. The Numeric Rating Scale (NRS), Oswestry Disability Index (ODI), Istanbul Low Back Pain Disability Index (ILBPDI), and the Short Form-36 (SF-36) were administered to all patients before and three weeks and three months after ESI. Results: The mean scores of all scales were significantly lower at three weeks and three months following ESI compared to the baseline scores. There were no significant differences between the mean scores at three weeks and three months. The NRS yielded the highest post-ESI change from baseline. Conclusion: Our study results showed that all scales used in this study were effective tools for the evaluation of outcomes of EPI in patients with low back pain. Although the NRS yielded the highest sensitivity for detecting change, evaluating functional state and quality of life is essential for multivariate analyses.
Keywords: Epidural steroid injection; low back pain; physical function; quality of life; DISABILITY; SURGERY